2020
DOI: 10.3390/ijms21165650
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Passive and Active Clinical Proton Beams

Abstract: Nowadays, the irradiation methodology in proton therapy is switching from the use of passively scattered beams to active pencil beams due to the possibility of more conformal dose distributions. The dose rates of active pencil beams are much higher than those of passive beams. The purpose of this study was to investigate whether there is any difference in the biological effectiveness of these passive and active irradiation modes. The beam qualities of double scattering and pencil beam scanning were measured do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This is in agreement with the study performed by Michaelidesova et al on normal human fibroblasts showing that PBS proton beam delivery was more efficient to produce double-strand breaks [49]. The same authors showed there were no differences in micronucleus frequency or γ-H2AX foci in cancer cell lines (medulloblastoma) at early times after PBS or DS proton irradiation [50]. It could be interesting to evaluate in vitro the ability of both delivery modes to induce long term genotoxicity in primary normal cells.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the study performed by Michaelidesova et al on normal human fibroblasts showing that PBS proton beam delivery was more efficient to produce double-strand breaks [49]. The same authors showed there were no differences in micronucleus frequency or γ-H2AX foci in cancer cell lines (medulloblastoma) at early times after PBS or DS proton irradiation [50]. It could be interesting to evaluate in vitro the ability of both delivery modes to induce long term genotoxicity in primary normal cells.…”
Section: Discussionsupporting
confidence: 91%
“…The spot size at isocenter was approximately 4.5 mm, and a 5 × 5 cm 2 field was created by scanning a single, narrow, monoenergetic proton-beam incident on the central axis with spots arranged in a uniform grid (same weight for all spots) with center-to-center spacing of 3 mm. Several studies have already made comparisons between these two modes 35 , 36 , and no significant differences were found for the LET d (dose-averaged linear energy transfer) values between the two modes. In this way, radiation field was the smallest possible to ensure the whole body irradiation and radiation time and linear energy transfer were equivalent for both delivery modes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, under the same conditions and in a homogeneous water phantom, the quantities related to both dose and adaptability properties were investigated and the superiority of spot scanning method in both dose transfer and adaptation was investigated. According to the literature, there are some controversies regarding the distal dose of PSPT against PBS systems (3,6,7); it might stem from the fact that the estimated physical/ biological dose in passive scattering proton therapy systems are dependent on the speci c scattering hardware's that are implemented in the beam trajectory. In this regard, the performance of multiple scattering designs should be simulated and further compared to provide a global conclusion about the advantages and disadvantages of active scanning proton therapy technique against passive scattering mode.…”
Section: Discussionmentioning
confidence: 99%
“…In PBS, multiple magnets in x and y directions, based on the charge of particles, are used to drift the beam and scanning the target volume spot by spot with a 3D narrow pencil beam (4,5). There are some studies in biological dose comparison between active and passive scanning proton therapy techniques in the cellular level (3,6,7). Gridley et al (7) compared cell response to active scanning and passive beam delivery techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation